Vertical Distribution of Mobile Trace Elements in Peat Deposits of the Lviv Region and Their Relationships with Physico-Chemical Properties - Yakovenko, Myroslava; Khokha, Yurii; Pavlyuk, Myroslav (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Problem statement: Peatlands act as natural geochemical barriers that accumulate various chemical elements, including heavy metals. The qualitative characteristics of peat and its potential applications directly depend on the spectrum and concentrations of elements present in it. For the peatlands of Ukraine, no systematic studies of mobile element forms or assessments of their relationships with local geochemical and physico-chemical gradients (pH, ash content, moisture) have yet been conducted. This gap highlights the need for systematic, methodologically unified investigations with broad spatial coverage and standardized procedures for data processing.Objective: To determine the levels, spatial (profile) distribution, and factors controlling the mobility of mobile forms of selected elements (Pb, As, Tl, Mo, Zn, Cd, Ni, Sb, Cu, Co, Mn, Cr, V) in the peats of the Lviv region; to clarify their relationships with physico-chemical properties of peat (pH, ash content, moisture content, organic matter content); and to identify depth-related trends and accumulation anomalies.Methods: Twenty-six samples were collected from the 0–140 cm depth interval at 20 cm steps (across three profiles), supplemented with samples from upper peat layers at additional sites. Mobile element forms were extracted with 0,2 M HCl and quantified by inductively coupled plasma atomic emission spectroscopy (ICP-AES). Ash content, moisture content, and pH were determined using arbitration methods according to DSTU standards. Statistical analyses were applied to evaluate the dependence of element concentrations on depth and physico-chemical parameters, to examine relationships among trace elements and other peat characteristics, and to assess potential sources of their accumulation.Results: Average concentrations of mobile forms of Pb, Zn, Cd, Cu, Ni, Mn, and Cr were 10,8; 15,5; 0,65; 3,86; 2,09; 16,6 and 0,96 ppm, respectively. Very high coefficients of variation (>80%) were observed for Pb, Cd, Tl, Mo, Sb, and Mn, indicating a mosaic spatial distribution. Maximum values of Pb (132,35 ppm) and Cd (8,88 ppm) occurred in the 60-80 cm horizon of the Honchary peatland, while elevated As (14,9 ppm) was found in the lower part of the Hamaliivka profile. In most samples, concentrations of mobile element forms were significantly lower than the approximate normal values for soils and the contamination thresholds established for arable soils in EU countries, indicating a generally low level of technogenic impact, despite the presence of local Pb and Cd anomalies. A positive relationship between the contents of most metals and ash content, and a negative relationship with organic matter content were identified. Significant correlations among Zn, Cu, Ni, Co, Mn, and V reflect shared sources and accumulation mechanisms. The strongest correlation (r ≈ 0,99) was observed between mobile Pb and Cd, confirming their similar geochemical behavior in peat.Conclusions: The results expand current knowledge on the geochemistry of European peatlands and, for the first time, characterize the mobile forms of several elements in the peats of the Lviv region. The peatlands of the region act as effective geochemical barriers for potentially toxic elements, while local deep anomalies of Pb–Cd and As may reflect both geogenic influences and historical atmospheric inputs. These findings refine the understanding of the geochemistry of Ukrainian peatlands and provide a basis for future assessments of environmental risks and the suitability of peat for economic use.